Professional flash mobile development : creating android and iphone applications - Wagner, Richard , 1966- (Indianapolis, Indiana : Wiley Publishing, 2011)
Provides information on developing native applications using Flash for the iPhone and Android-based mobile devices.
1. Introducing flash development for mobile devices -- 2. Setting up your development environment -- 3. Building and installing VanillaApp -- 4. Rethinking action script programming -- 5. Multitouch API -- 6. Detecting motion with accelerometer -- 7. Implementing auto orientation -- 8. Geolocation API -- 9. Service integration using URL protocols -- 10. Android camera, camera roll, and microphone -- 11. File management -- 12. Local databases -- 13. Remote debugging -- 14. Submitting descriptor settings
"Wrox programmer to programmer"--Cover
Includes index
Keywords: Android (Electronic resource); Flash (Computer file); iPhone OS; Application software -- Development; Mobile computing